544 Mentoring medical students- an opportunity to connect with and inspire the next generation. (17th August 2022) - Scott, Maura; Bell, Alison; Stewart, Gemma; Stefkova, Katarina; Graham, Marcus; Richardson, Julie; Lewis, Julie
Abstract : Aims: The RCPCH recognises that 'access to effective mentoring support is likely to become increasingly important in the development of paediatricians.' Paediatric trainees in Northern Ireland (NI) have a well-established peer-mentoring programme which continues to provide valuable support to trainees. Feedback from medical students in NI suggested that those keen to pursue a career in Paediatrics would benefit from a trainee mentoring programme. As #choosepaediatrics is a significant RCPCH strategic priority to encourage recruitment to our specialty we set out to provide medical students with the opportunity to be 'mentored' by a trainee paediatrician. It was our hope that the mentoring programme would help give medical students an idea of our specialty, how to apply, opportunities available and an overview of what life is like as a paediatrician. Methods: The NI Paediatric Mentoring programme collaborated with the Child Health Society from Queen's University Belfast. This society, ran by enthusiastic medical students keen to pursue a career in paediatrics, was pivotal in the recruitment of medical students. Following an initial scoping exercise with medical students, a pilot mentoring programme was founded with paediatric trainees from all levels of training and final year medical students. The programme was advertised via email and social media. Mentees had the opportunity to review an anonymous profile of each mentor and rank their preferred mentor. The profile detailed special interests, work patterns, location and a brief summary paragraph about the mentor. Following the matching process contact details were provided and the mentee was encouraged to initiate the mentoring journey. Results: This small, pilot student mentoring programme had five successful mentoring pairings. It was found to be hugely beneficial for both the mentee and their mentor. All student mentees rated the programme as 'quite' or 'very' beneficial with 80% of mentees suggesting that they would 'recommend to a friend.' Common topics of conversation included careers advice, exams, the application process, life as a foundation year doctor and work life balance. Students commented that it was 'extremely useful to hear what paediatric training is like in terms of work life balance.' Conclusion: Paediatrics is in the midst of a recruitment and retention crisis. We need to engage with medical students to help promote our specialty otherwise (as noted by the RCPCH) these issues will threaten the safety of children's health. This was a small project which has been very well received by all participants. Following this feedback, the programme is to be expanded and offered to all medical students within their clinical years. We have formally partnered with our training deanery to utilise the online 'Mentornet' software platform and to facilitate mentoring training for all interested paediatric trainees in Northern Ireland. We hope this will mutually benefit our trainees whilst encouraging the future paediatricians of Northern Ireland.